2018
DOI: 10.3892/ijmm.2018.3913
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA C5orf66-AS1 prevents oral squamous cell carcinoma through inhibiting cell growth and metastasis

Abstract: Oral squamous cell carcinoma (OSCC) is a major cancer type in the head and neck region. Recent studies have reported a marked rise in the incidence of OSCC. The present study was performed to better understand the roles that long non-coding RNAs (lncRNAs) serve in OSCC carcinogenesis. The levels of the lncRNA C5orf66 antisense RNA 1 (C5orf66-AS1) and of cytochrome c1 (CYC1) in OSCC tissues and cells were measured through reverse transcription-quantitative polymerase chain reaction. In addition, the levels of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Shen et al (2018) reported that higher expression of AC026166.2-001 suppressed cell proliferation and migration in LSCC cells, inhibited cells cycle, and supported cell apoptosis in laryngeal cancer. Also other lncRNAs are upregulated in HNSCC and may display oncogenic properties, such as ZFAS1 (Kolenda et al 2019), PVT1 (Yu et al 2018), CASC9 (Sassenberg et al 2019), TUG1 (Zhang et al 2018b), MIAT (Zhong et al 2019), SNHG20 (Wu et al 2019), or RGMB-AS (Xu and Xi 2019), or downregulated and may act as tumor suppressor genes, such as STR5-AS (Wang et al 2019a), C5orf66-AS1 (Lu et al 2018), AC012456.4 (Hu et al 2018b), LINC01133 (Kong et al 2018), ZNF667, and ZNF667-AS1 (Meng et al 2019).…”
Section: Tumor Suppressor Mirnasmentioning
confidence: 99%
“…Shen et al (2018) reported that higher expression of AC026166.2-001 suppressed cell proliferation and migration in LSCC cells, inhibited cells cycle, and supported cell apoptosis in laryngeal cancer. Also other lncRNAs are upregulated in HNSCC and may display oncogenic properties, such as ZFAS1 (Kolenda et al 2019), PVT1 (Yu et al 2018), CASC9 (Sassenberg et al 2019), TUG1 (Zhang et al 2018b), MIAT (Zhong et al 2019), SNHG20 (Wu et al 2019), or RGMB-AS (Xu and Xi 2019), or downregulated and may act as tumor suppressor genes, such as STR5-AS (Wang et al 2019a), C5orf66-AS1 (Lu et al 2018), AC012456.4 (Hu et al 2018b), LINC01133 (Kong et al 2018), ZNF667, and ZNF667-AS1 (Meng et al 2019).…”
Section: Tumor Suppressor Mirnasmentioning
confidence: 99%
“…Guo et al 21 reported that C5orf66-AS1 was upregulated in esophageal cancer cells, the expression of proliferation-related indicators Ki-67 and PCNA was downregulated, the expression of EMT-related proteins N-cadherin and Vimentin was downregulated, and the E-cadherin involved in the invasion and metastasis pathway was upregulated, suggesting that C5orf66-AS1 inhibited the proliferation and metastasis of esophageal cancer cells. 21 Lu et al 19 reported that CYC1 was negatively regulated by C5orf66-AS1 in oral squamous cell carcinoma, and the biological behavior (invasion, metastasis, proliferation, and apoptosis) could be reversed by knocking down CYC1. Rui et al 23 reported that C5orf66-AS1 could promote the proliferation, invasion, and metastasis of cervical cancer cells and inhibit the apoptosis of cervical cancer cells by competing with RING1 in combination with miR-637.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 These characteristics provide a theoretical basis for considering lncRNAs as biomarkers for cancer. It has been reported that lncRNA can participate in series of pathological processes in tumorigenesis, for instance, inflammatory response, 17 autophagy, 18 pyroptosis, 19 metabolic reprogramming, 18 as well as crosstalk between immune cells and tumor cells 20 and immunotherapy resistance. 21 The extensive functions of lncRNAs suggest extremely valuable for research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lncRNA c5orf66-as1 (also known as Epist and ctc-276p9.1) is located in human chromosome 5q31.1. Studies have shown that the expression of c5orf66-as1 is downregulated in esophageal squamous cell carcinoma, oral squamous cell carcinoma, and cardiac carcinoma [80][81][82][83], meaning that this lncRNA may act as a tumor suppressor, and that it constitutes a potential marker for patient prognosis and survival. Interestingly, Rui et al [84] reported that in cervical cancer tissues and cells, c5orf66-as1 is significantly upregulated.…”
Section: C5orf66-as1mentioning
confidence: 99%